2013
DOI: 10.1371/journal.pone.0069617
|View full text |Cite
|
Sign up to set email alerts
|

Low Immunogenicity of Neural Progenitor Cells Differentiated from Induced Pluripotent Stem Cells Derived from Less Immunogenic Somatic Cells

Abstract: The groundbreaking discovery of induced pluripotent stem cells (iPS cells) provides a new source for cell therapy. However, whether the iPS derived functional lineages from different cell origins have different immunogenicity remains unknown. It had been known that the cells isolated from extra-embryonic tissues, such as umbilical cord mesenchymal cells (UMCs), are less immunogenic than other adult lineages such as skin fibroblasts (SFs). In this report, we differentiated iPS cells from human UMCs and SFs into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 63 publications
0
39
1
Order By: Relevance
“…Cell viability was examined by trypan blue exclusion staining. Co-culture experiments were carried out as described previously [30,33,34]. Culture volumes of 100 µL per well in a 96-well plate were used, with the ratio of antigen cells to PBMCs kept at 1 : 100.…”
Section: Isolation Of Pbmcs and T Cells And Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability was examined by trypan blue exclusion staining. Co-culture experiments were carried out as described previously [30,33,34]. Culture volumes of 100 µL per well in a 96-well plate were used, with the ratio of antigen cells to PBMCs kept at 1 : 100.…”
Section: Isolation Of Pbmcs and T Cells And Proliferation Assaymentioning
confidence: 99%
“…NPC differentiation from hESCs and hiPSCs derived from both SFs and UCs was performed as described previously [26,30,35,36]. The typical neural rosettes were blown off and picked out to produce a neural sphere consisting of Figure 1A).…”
Section: Npc Differentiation From Hescs/hipscsmentioning
confidence: 99%
“…The HN4 cell line was cultured originally on mixed MEFs and HFFs feeder (MFCs, MEFs: HFFs = 1:1) as previously described (Li et al, 2010; Liu et al, 2013). P96 cell line was cultured originally on HFFs with mTeSR1 medium (STEMCELL Technologies, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Though Zhao et al reported immunogenicity of murine iPSCs as compared to ESCs due to the abnormal expression of antigens based on the epigenetic differences between iPSCs and ESCs or mutations in the coding sequences of iPSCs [74], other studies have found only negligible immunogenicity of in vitro -differentiated iPSCs [75-77]. Thus far, the majority of studies have not demonstrated acquired immune reactions against autologous iPSCs and their derivatives.…”
Section: Immune Reaction Against Ipscsmentioning
confidence: 99%